Eight Aneurysms Handbook of Cerebral Aneurysm Embolization - Ren, Zeguang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book introduces the basic tenets and technique skills for endovascular embolization and provides the most up-to-date technical advancements, treatment strategy evolution, and literature review related to the endovascular treatment of brain aneurysms. The most special feature of this book is how the content is organized. The morphology, instead of the location, dictates the treatment strategy applied and procedure skills required for the endovascular treatment of brain aneurysms. Hence, the book is structured with a new conceptual way of classifying aneurysms into eight different types based on the morphological characteristics of brain aneurysms. The specific technical skills and treatment strategies for these different aneurysm categories are described separately in their own chapters. Another important feature of the book is the combination of detailed technical descriptions of the skills, strategies, and advancement in the field accompanied with case presentations. The large and comprehensive collection of the case presentations further enhances the points in the text. This book can be used as a handbook on endovascular treatment of brain aneurysms. It can also help physicians in the early careers of these subspecialties for their daily practice and board preparation. The text will provide the most up-to-date knowledge for more experienced endovascular neurosurgeons and interventionalists on the topics of new techniques and endovascular products. Additionally, it can also serve as a practice guidance resource for nurse practitioners and physician assistants of the above subspecialties. .
Why the Brain is classified into eight types, and what are they? -- Anticoagulation and antiplatelet treatment related to endovascular treatment of aneurysms -- Complications of aneurysm embolization and its prevention -- Trans-femoral access -- Trans-radial access -- Transbrachial access -- Transcervical Access -- Narrow neck aneurysm -- Wide neck aneurysm -- Blood Blister like and small aneurysms -- Fusiform/Dissecting Aneurysm -- Recurrent/Residual Aneurysm -- Large and giant aneurysms -- Pseudoaneurysms/arterial injury -- Infectious aneurysm (mycotic aneurysm).
Keywords: Nervous system$1 (BSurgery.s; Neurosurgery; Intracranial Aneurysm -- therapy; Embolization, Therapeutic; Case Reports